Scenarios to promote mathematical competences in the university - Paredes, Rosa Eulalia Cardoso (2017)
This communication will show a view of scenarios to promote mathematical competences: general, referred to the mathematical content and the scope of demand, in students of the first cycle of General Studies of Letters that includes careers in the Social Sciences (Anthropology, Sociology) and Humanities ( Literature, Psychology, History, Geography, Linguistics, Philosophy) of a Peruvian university, from teaching experiments framed in the Realistic Mathematical Education (EMR) of Freudenthal (1991), planned, experimented and redesigned from the methodology of teaching design (Kelly, 2000; Rubio, 2012), considering the didactic suitability of EOS (Godino, Batanero and Font, 2009; Rubio, 2012). That is, we will show the routes that mathematical content must follow to reach future non-mathematical professionals (Gaita et al., 2009).